VD_FINDINFO HC / 2025 / 136 vom 27. Februar 2025 - VD Tribunal cantonal (2025)
JUGEMENT DE DIVORCE, MESURE PROVISIONNELLE, DÉBITEUR, ACTION EN MODIFICATION, DIRECTIVEINJONCTION | 291 CC, 276 al. 1 CPC (CH)